Reflections of the North Adriatic Stone-Carving Workshops in Early Medieval Sisak - Belošević, Nikolina; Dujmović, Danko (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The paper contributes to the interpretation of five fragments of early medieval sculpture and two capitals from the 5th century found around Sisak. Through the historical context and the analysis of the formal elements of early medieval sculpture, the authors discuss influences that came to the Pannonia Inferior from the cultural centres in the northern Adriatic, thus reflecting the specific circumstances in which Sisak is mentioned again after the late antique period in written sources of the early 9th century.
Keywords: Sisak; Siscia; early Middle Ages; stone sculpture fragments; North Adriatic; stone-carving workshops; Pannonia